2016
DOI: 10.1080/14767058.2016.1260115
|View full text |Cite
|
Sign up to set email alerts
|

Inter-pregnancy interval and adverse outcomes: Evidence for an additional risk in health disparate populations

Abstract: Rates of less than optimal IPI were high in this population already experiencing significant maternal-child health disparities, with short IPI a particular risk factor for poor outcomes for the most disadvantaged women, suggesting yet another precursor for adverse birth outcomes in those already most at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 21 publications
2
68
1
Order By: Relevance
“…In the three fair‐quality studies, interpregnancy intervals of <6 months were consistently associated with significantly increased risks of infant mortality and neonatal mortality, with point estimates ranging from aOR = 1.44 (95% CI 1.06, 1.95) to aOR = 2.23 (95% CI 1.19, 4.16) . There were significantly increased risks in one study for interpregnancy intervals of 6‐11 months for infant mortality (aOR = 1.68) and neonatal mortality (aOR = 1.62); and in the same study for interpregnancy intervals of 12‐17 months for infant mortality (aOR = 1.48) and neonatal mortality (aOR = 1.49) …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In the three fair‐quality studies, interpregnancy intervals of <6 months were consistently associated with significantly increased risks of infant mortality and neonatal mortality, with point estimates ranging from aOR = 1.44 (95% CI 1.06, 1.95) to aOR = 2.23 (95% CI 1.19, 4.16) . There were significantly increased risks in one study for interpregnancy intervals of 6‐11 months for infant mortality (aOR = 1.68) and neonatal mortality (aOR = 1.62); and in the same study for interpregnancy intervals of 12‐17 months for infant mortality (aOR = 1.48) and neonatal mortality (aOR = 1.49) …”
Section: Resultsmentioning
confidence: 89%
“…Infant mortality was assessed in four studies (three cohort studies and one case‐control study) (Figure B) . A good‐quality study reported an aOR of 3.6 (95% CI 1.2, 10.7) for neonatal death (death within the first four weeks of life) for interpregnancy intervals <6 vs 18‐23 months …”
Section: Resultsmentioning
confidence: 99%
“…Since the end of the one‐child policy in China, longer IPIs have been associated with higher risks of preterm delivery and term low birth weight in the second pregnancy independent of maternal age . In the USA, by contrast, short IPI was found to be a risk factor for poor neonatal outcomes among socially disadvantaged women . In the present study, the IPI between the last cesarean delivery and the start of the index pregnancy was longer among women presenting with placenta percreta than among those with non‐accreta previa ( P =0.049).…”
Section: Discussionmentioning
confidence: 45%
“…[4][5][6] Given that women with intellectual and developmental disabilities are more likely than their peers to experience marginalization in the form of poverty, isolation, and medical or mental illness, [14][15][16][17] it is not surprising that their risk for rapid repeat pregnancy was elevated in the unadjusted analyses. Notably, the importance of low income and social assistance in the adjusted and stratified analyses supports the idea that social vulnerability -whether at an individual or system level -explains the impact of disability status on risk of rapid repeat pregnancy.…”
Section: Continuity Of Primary Carementioning
confidence: 99%
“…2 Nevertheless, high rates of rapid repeat pregnancy in North America, as well as research showing that as many as 55% of such pregnancies are unintended, 3 make prevention of rapid repeat pregnancy a public health priority. Adolescents and women with low education or income have been shown to be at high risk for rapid repeat pregnancy [4][5][6] and have been the focus of public health efforts. 3 Women with intellectual and developmental disabilities, who exhibit some of the same risk factors for rapid repeat pregnancy, such as suboptimal access to contraception and other family planning services, 7 have yet to be studied.…”
mentioning
confidence: 99%